Quantitative Analysis of Land Use Classification in Agricultural and Forest Areas - Matuk, Olga (Geomatics and Environmental Engineering, 2022)
The article deals with the research on the quantitative classification of land use, which directly affects the amount of land use data collected in the real estate cadastre. For the purpose of this article, the cadastral systems of seven European countries – Austria, Bulgaria, Estonia, Spain, Lithuania, Germany and Poland – have been examined, taking into account how detailed is the classification in agricultural and forest areas. The research covered the provisions of legal acts applicable in the researched seven European countries and made available in national languages by the government bodies. The article asks the following three questions: 1) whether the researched countries adopted the same approach to isolating classes of items related to agricultural and forest areas; 2) whether the researched countries feature the same number of classes of items recorded at various levels of detail; 3) what is the percentage of the distinguished item classes of land uses in the agricultural and forest areas in relation to all of the distinguished item classes at all the levels of detail. The conducted research can be used as a material supporting works consisting of the modernization of the functioning of land registration in the real estate cadastre in Poland.